2019
DOI: 10.3390/ijms20194676
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Cadmium and Zinc Phytotoxicity Alter DNA Methylation Levels to Confer Heavy Metal Tolerance in Wheat

Abstract: Being a staple food, wheat (Triticum aestivum) nutritionally fulfills all requirements of human health and also serves as a significant link in the food chain for the ingestion of pollutants by humans and animals. Therefore, the presence of the heavy metals such as lead (Pb) and cadmium (Cd) in soil is not only responsible for the reduction of wheat crop yield but also the potential threat for human and animal health. However, the link between DNA methylation and heavy metal stress tolerance in wheat has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 65 publications
0
47
1
Order By: Relevance
“…Notably, the methylation level at the promoter of a stress-responsive gene TaFLS1 (encoding a flavonol synthase) was lower in the salinity tolerant wheat cultivar SR3 than in salinity susceptible wheat cultivar JN177, which is opposite to the higher gene expression in SR3 than in JN177, suggesting that DNA methylation might get involved in regulation of wheat salinity tolerance [25]. Besides, the modulation of metal-stress response by DNA methylation is reported in wheat and barley [37,38]. In heavy metal detoxifications, the multidrug resistance-associated protein (MRP) type ATP-binding cassette (ABC) transporters play important roles, which also involve in other plant biological processes such as pathogen response and development [39][40][41][42].…”
Section: Dna Methylationmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the methylation level at the promoter of a stress-responsive gene TaFLS1 (encoding a flavonol synthase) was lower in the salinity tolerant wheat cultivar SR3 than in salinity susceptible wheat cultivar JN177, which is opposite to the higher gene expression in SR3 than in JN177, suggesting that DNA methylation might get involved in regulation of wheat salinity tolerance [25]. Besides, the modulation of metal-stress response by DNA methylation is reported in wheat and barley [37,38]. In heavy metal detoxifications, the multidrug resistance-associated protein (MRP) type ATP-binding cassette (ABC) transporters play important roles, which also involve in other plant biological processes such as pathogen response and development [39][40][41][42].…”
Section: Dna Methylationmentioning
confidence: 99%
“…As an important epigenetic process, DNA methylation generally regulates plant responses to environmental stresses such as salinity and heavy metal stress in wheat and barley [36,37]. For instance, a recent report showed that DNA methylation could regulate the expression of a salinity-responsive gene in bread wheat [25].…”
Section: Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…The main roles of heavy metals in plant metabolism are the basis of their involvement in reduction/oxidation procedures [4]. Cadmium toxicity is also associated with diminished plant growth, enzyme activity, and metabolism [5].…”
Section: Introductionmentioning
confidence: 99%